Jawabanmu

2014-03-26T07:48:02+07:00
Fungsi kuadrat y = ax² + bx + c

(-1,5) ⇒ 5 = a - b + c  ...... (i)
(2,4) ⇒ 4 = 4a + 2b + c ....(ii)
(4,0) ⇒ 0 = 16a + 4b + c...(iii)

eliminasi (i) & (ii),
5 = a - b + c        
4 = 4a + 2b + c      -
1 = -3a -3b .... (iv)

eliminasi  (i) & (iii),
4 = 4a + 2b + c
0 = 16a + 4b + c     -
4 = -12a - 2b
2 = - 6a - b .... (v)
 
eliminasi  (iv) & (v),
1 = -3a -3b   x2 ⇒  2 = -6a -6b
2 = - 6a - b   x1 ⇒ 2 = -6a - b    -
                           0 = - 5b ⇒ b = 0

1 = -3a - 3b
1 = -3a - 0
a = - \frac{1}{3}

5 = a - b + c 
5 = - \frac{1}{3} - 0 + c 
c = 5 \frac{1}{3}  

maka Y = - \frac{1}{3} x^{2}  +  \frac{16}{3}


1 5 1